The Role Of Islamic Capital Market In Economic Growth Economy In Indonesia - Sefhia Lara Fatricia (Jurnal Akuntansi, Manajemen, Ekonomi Islam, 2024)
This research aims to determine the role of the Islamic capital market in the rate of economic growth in Indonesia. Based on the data analysis and discussion that has been carried out, the following conclusions can be drawn: the results of the analysis show that the level of role of the Islamic capital market in the rate of economic growth in Indonesia. However, the percentage figures that have been calculated show that the role of the Islamic capital market in the rate of economic growth in Indonesia must continue to be increased. Investment knowledge has a significant influence on the role of the Islamic capital market in the rate of economic growth in Indonesia